Effect of strength training on jump-landing biomechanics in adolescent females - Herman, D. C.; Pritchard, K. A.; Cosby, N. L.; Selkow, N. M. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Sex-based differences in neuromuscular characteristics relevant to anterior cruciate ligament (ACL) injury risk may arise as compensation for divergent strength development during puberty. Strength training during this period may prevent the development of these undesirable neuromuscular characteristics. Hypothesis: Strength-trained middle school girls will have improved jump-landing biomechanics compared with control participants. Study Design: Cohort study. Level of Evidence: Level 3. Methods: Maximum voluntary isometric contraction in hip extension and abduction and knee extension and flexion as well as Landing Error Scoring System (LESS) scores were collected for healthy female middle school students of grades 6 to 8. Strength-training participants (STR: N = 30; height, 1.63 ± 0.07 m; mass, 48.1 ± 7.6 kg; age, 12.5 ± 1.0 y) were matched with control participants (CON: N = 30; height, 1.60 ± 0.09 m; mass, 47.2 ± 8.9 kg; age, 12.6 ± 0.9 y). The training consisted of a 6-month strength-training program administered through a gym class curriculum that targeted the lower extremity. A repeated-measures mixed-model analysis of variance was used for comparisons between groups and across time (a = 0.05). Stepwise linear regression was used to examine the relationship between strength change and LESS score change. Results: Strength values (N·m/kg) increased across time and to a greater degree in STR for hip extension (baseline 3.98 ± 1.15 vs follow-up 4.77 ± 1.80), hip abduction (4.22 ± 1.09 vs 5.13 ± 2.55), and knee flexion (3.27 ± 0.62 vs 3.64 ± 1.40) compared with CON. LESS grades significantly decreased across time in STR (5.58 ± 1.21 vs 4.86 ± 1.44) and were significantly lower than CON (5.98 ± 1.42) at follow-up (P < 0.001). The change in hip extension and knee extension strength explained 67% of the variance (P < 0.001) in the LESS change score in the STR group. Conclusion: A school-based strength-training program that focused on hip and knee musculature significantly improved jump-landing biomechanics (as determined by LESS) relevant to ACL injury risk. Further investigation using different strength-training approaches in this age group is warranted. Clinical Relevance: Strength training during adolescence holds promise as an injury prevention program. The use of a school-based approach is novel and may represent a robust opportunity for injury prevention programs, as physical education class is often mandatory in this age group.